2008
DOI: 10.1007/s00586-008-0790-y
|View full text |Cite
|
Sign up to set email alerts
|

Aprotinin in pediatric neuromuscular scoliosis surgery

Abstract: Reduction of blood transfusions in patients with neuromuscular scoliosis can decrease potential complications such as immune suppression, infection, hemolytic reaction and viral transmission. Aprotinin (Trasylol Ò , Bayer), an antifibrinolytic, has proven to be effective in reducing blood loss in cardiac and liver surgery, but little data exists in patients undergoing spinal fusion for neuromuscular scoliosis. The purpose of this study was to evaluate the safety and efficacy of aprotinin in pediatric neuromusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…4 , 7 Thompson et al 11 studied the role of EACA in neuromuscular scoliosis and found that it reduced blood loss and transfusion requirements. Kasimian et al 12 reported similar results with the use of aprotinin in 14 patients. Shapiro et al 13 showed the effi cacy of TXA in reducing intraoperative blood loss and transfusions in patients with DMD scoliosis.…”
Section: Comparison Of Naf Eaca and Txa Groupssupporting
confidence: 76%
“…4 , 7 Thompson et al 11 studied the role of EACA in neuromuscular scoliosis and found that it reduced blood loss and transfusion requirements. Kasimian et al 12 reported similar results with the use of aprotinin in 14 patients. Shapiro et al 13 showed the effi cacy of TXA in reducing intraoperative blood loss and transfusions in patients with DMD scoliosis.…”
Section: Comparison Of Naf Eaca and Txa Groupssupporting
confidence: 76%
“…Kasimian et al [16] have shown that the use of an antifibrinolytic (Aprotinin) resulted in decreased blood loss and decreased rate of transfusions in children with neuromuscular scoliosis undergoing extensive spinal fusion. In the experience it was intraoperatively used Caprolisin Ò (aminocaproic acid) with mean blood loss of 1200 ± 400 ml.…”
Section: Discussionmentioning
confidence: 99%
“…The use of aprotinin reduced perioperative blood loss and need for transfusion in neuromuscular scoliosis patients undergoing extensive spinal surgery and saved an average of $8,577 per patient [48].…”
Section: Analysis and Findings Of Ees In Orthopedic Surgery And Traummentioning
confidence: 99%